(untitled) (Journal of Educational Sciences, 2025)
This article is devoted to examining the impact of political science courses on bachelor students’ political engagement and participation. The main objective of this study is to compare which teaching method in political science is most effective in enhancing students’ political activity and agency. Therefore, the authors analyze students’ political awareness, their involvement in political and civic activities, self-assessment of political efficacy, perceptions of teaching approaches, and engagement with the course. To achieve this, methods such as observation, analysis of instructional materials, surveys, and focus group discussions were employed. The authors concludes that the teaching methods used in class have varying effects on students’ political activity. Simulation and discussion-based methods have the greatest impact on students’ engagement and political agency. Furthermore, discussions and simulations prove to be more effective than traditional lectures in fostering new digital forms of political participation. The results of the study have considerable practical significance as they may facilitate further improvement of educational programs on political science and the teaching materials. The findings presented in this article can be used by education professionals while developing curricular and syllabi helping them to choose the most effective teaching strategies that would stimulate political participation of students. Key words: political participation, students, political science, political activity, teaching methods.